JUAL BELI KREDIT DITINJAU DARI PERSEFEKTIF HUKUM ISLAM - Adanan Murroh (Institut agama islam negeri Padangsidimpuan, 2016)
Credit payment is now the most popularway of payment among the socialty, because this kind of trade offers many advantages one of them is bringing needed things without cash paying. But many religious leaders have different opinionabout the credit payment law some of them give their agreement but others do’not agree with it. However most of the relegius leaders allow the credit payment system. This opinion is based on the lafaz nash whicl allows any payment system. But in other hand, for whou disagree with system argue that there is riba in this payment system.